2014
DOI: 10.1152/ajpregu.00551.2013
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol, but not testosterone, heightens cortisol-mediated negative feedback on pulsatile ACTH secretion and ACTH approximate entropy in unstressed older men and women

Abstract: How sex steroids modulate glucocorticoid feedback on the hypothalamic-pituitary-corticotrope (HPC) unit is controversial in humans. We postulated that testosterone (T) in men and estradiol (E2) in women govern unstressed cortisol-mediated negative feedback on ACTH secretion. To test this hypothesis, 24 men and 24 women age 58 ± 2.4 yr were pretreated with leuprolide and either sex steroid (E2 in women, T in men) or placebo addback. Placebo or ketoconazole (KTCZ) was administered overnight to inhibit adrenal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 45 publications
2
14
1
Order By: Relevance
“…Cortisol is not considered to be synthesized in the placenta, so it is unlikely that this contributes to the lower cortisol we found in very severely obese pregnancy. In contrast to our findings of lower cortisol and lower estrogen in very severely obese pregnant women, a small study in postmenopausal women suggested that higher estrogen levels may magnify the negative feedback of cortisol on the HPAA in postmenopausal women, leading to lower cortisol levels (35). To the best of our knowledge, there are no other data describing the effects of estrogen on cortisol in severely obese pregnant women.…”
Section: Stirrat LI Et Al 2015 11contrasting
confidence: 99%
“…Cortisol is not considered to be synthesized in the placenta, so it is unlikely that this contributes to the lower cortisol we found in very severely obese pregnancy. In contrast to our findings of lower cortisol and lower estrogen in very severely obese pregnant women, a small study in postmenopausal women suggested that higher estrogen levels may magnify the negative feedback of cortisol on the HPAA in postmenopausal women, leading to lower cortisol levels (35). To the best of our knowledge, there are no other data describing the effects of estrogen on cortisol in severely obese pregnant women.…”
Section: Stirrat LI Et Al 2015 11contrasting
confidence: 99%
“…Because of a higher pulse frequency, no sex difference emerged for total cortisol secretion. Although the role of (premenopausal) estrogen is not so clear ( 18 ), in older adults short-term administration of estradiol, but not testosterone, heightens cortisol-mediated inhibition of pulsatile ACTH secretion ( 15 ). In principle, therefore, an estrogenic milieu could lower mean cortisol in premenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…However, when artificially hypogonadal males (i.e., due to Leuprolide administration) were subsequently administered T compared to placebo, they showed a significantly dampened C secretion but paradoxically also an increased CRH-stimulated ACTH secretion, indicating that the effect of T on the HPA-axis is likely to be exerted peripherally instead of centrally (Rubinow et al, 2005). In fact, since peripherally stimulated C secretion is known to provide feedback autoregulation on HPA-axis activity, this finding may actually suggest that T dampens HPA-axis feedback inhibition and thus prolongs its activation (e.g., Sharma et al, 2014). Accordingly, a number of studies have reported tight coupling between the HPA- Thus, in addition to a mutually inhibitory effect, there are likely also some mutually excitatory effects (see also Sharma, Aoun, Wigham, Weist, & Veldhuis 2014).…”
Section: Clarifying the Heterogeneity In Psychopathic Samples 56mentioning
confidence: 99%